Spreadsheet error detection: an empirical examination in the context of Greece - Maditinos, Dimitrios; Chatzoudes, Dimitrios; Tsairidis, Charalampos (Business, Management and Economics Engineering, 2012)
The personal computers era made advanced programming tasks available to end users. Spreadsheet models are one of the most widely used applications that can produce valuable results with minimal training and effort. However, errors contained in most spreadsheets may be catastrophic and difficult to detect. This study attempts to investigate the influence of experience and spreadsheet presentation on the error finding performance by end users. To reach the target of the study, 216 business and finance students participated in a task of finding errors in a simple free cash flow model. The findings of the study reveal that presentation of the spreadsheet is of major importance as far as the error finding performance is concerned, while experience does not seem to affect students on their performance. Further research proposals and limitations of the study are, moreover, discussed.